1999
DOI: 10.1002/(sici)1098-2752(1999)19:3<135::aid-micr3>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Brief ex vivo perfusion with heparinized and/or citrated whole blood enhances tolerance of free muscle flaps to prolonged ischemia

Abstract: This study investigated the use of heparinized and/or citrated whole blood as a perfusate for enhancing muscle tolerance to warm ischemia. Unilateral cutaneous trunci muscle flaps were harvested from Sprague-Dawley rats and stored for 10 hr at 22-24 degrees C prior to transplantation to the groin. One group served as a non-perfused control. In three experimental groups, the flaps were hand-perfused ex vivo with 1.0 ml of heparinized, citrated, or heparinized and citrated autogenous whole blood at physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
(38 reference statements)
0
7
0
1
Order By: Relevance
“…However, complications and even complete failure because of partial or complete necrosis of the transplanted tissue may occur in 5% of all cases . Tissue damage caused by prolonged ischaemia after harvesting the flap is still one of the limiting factors . At this time, the standard procedure in reconstructive surgery for flap preservation is cold storage, often in addition with a singular flush of the tissue with a saline solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, complications and even complete failure because of partial or complete necrosis of the transplanted tissue may occur in 5% of all cases . Tissue damage caused by prolonged ischaemia after harvesting the flap is still one of the limiting factors . At this time, the standard procedure in reconstructive surgery for flap preservation is cold storage, often in addition with a singular flush of the tissue with a saline solution.…”
Section: Introductionmentioning
confidence: 99%
“…At this time, the standard procedure in reconstructive surgery for flap preservation is cold storage, often in addition with a singular flush of the tissue with a saline solution. In the past, numerous studies have been set‐up to learn more about causes of ischaemia‐related tissue damage and optimizing conservation protocols . Even though most of these studies revealed encouraging results, at present none of them essentially changed the standard procedure in daily clinical routine.…”
Section: Introductionmentioning
confidence: 99%
“…The rinsing of the flap tissue with heparin solution as performed in this study forms an inner anticoagulant surface. It is known that heparin influences rheological properties of blood and that it protects free flaps from ischemia/reperfusion injury [9,11,13,19,24,28]. Former experiments with neurovascular epigastric skin island flaps in the rat model demonstrate that systemic treatment with 300 I.U./kg of heparin increases the tissue tolerance to venous occlusion and significantly improves flap survival [29].…”
Section: Discussionmentioning
confidence: 99%
“…University of Wisconsin (UW) solution has been widely used in the setting of liver, pancreas, and kidney transplantation. However, it is arguable whether or not UW solution is beneficial for preserving skeletal muscle [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%